A new pedigree with thrombomodulin‐associated coagulopathy in which delayed fibrinolysis is partially attenuated by co‐inherited TAFI deficiency. (23rd July 2020) - Westbury, Sarah K.; Whyte, Claire S.; Stephens, Jonathan; Downes, Kate; Turro, Ernest; Claesen, Karen; Mertens, Joachim C.; Hendriks, Dirk; Latif, Anne‐Louise; Leishman, Emma J.; ,; Mutch, Nicola J.; et al.
Abstract: Background: Thrombomodulin‐associated coagulopathy (TM‐AC) is a rare bleeding disorder in which a single reported p.Cys537* variant in the thrombomodulin gene THBD causes high plasma thrombomodulin (TM) levels. High TM levels attenuate thrombin generation and delay fibrinolysis. Objectives: To report the characteristics of pedigree with a novel THBD variant causing TM‐AC, and co‐inherited deficiency of thrombin‐activatable fibrinolysis inhibitor (TAFI). Patients/methods: Identification of pathogenic variants in hemostasis genes by next‐generation sequencing and case recall for deep phenotyping. Results: Pedigree members with a previously reported THBD variant predicting p.Pro496Argfs*10 and chain truncation in TM transmembrane domain had abnormal bleeding and greatly increased plasma TM levels. Affected cases had attenuated thrombin generation and delayed fibrinolysis similar to previous reported TM_AC cases with THBD p.Cys537*. Coincidentally, some pedigree members also harbored a stop‐gain variant in CPB2 encoding TAFI. This reduced plasma TAFI levels but was asymptomatic. Pedigree members with TM‐AC caused by the p.Pro496Argfs*10 THBD variant and also TAFI deficiency had a partially attenuated delay in fibrinolysis, but no change in the defective thrombin generation. Conclusions: These data extend the reported genetic repertoire of TM‐AC and establish a common molecular pathogenesis arising from high plasma levels of TM extra‐cellular domain. The data further confirm that the delay in fibrinolysis associated with TM‐AC is directly linked to increased TAFI activation. The combination of the rare variants in the pedigree members provides a unique genetic model to develop understanding of the thrombin‐TM system and its regulation of TAFI.